Deaths and diseases: The impact of Covid-19 in Indonesian stock return - Kris Brantas Abiprayu; Ascariena Rafinda; Bayu Wiratama (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2023)
This study aims to determine whether COVID-19 can have an impact on the stock market returns in the Indonesia Stock Exchange, especially on the LQ45 Index. This study uses secondary data, spesifically confirmed positive cases of COVID-19 and cases of death due to COVID-19 during the period 1 April to 30 June 2020 obtained from the official website of the Komite Penanganan COVID-19 dan Pemulihan Ekonomi Nasional - SATGAS Penanganan COVID-19. This study uses a panel data regression method to test the hypothesis. Our findings show that confirmed positive cases of COVID-19 and cases of death due to COVID-19 have a positive effect on stock market returns on the LQ45 Index.